Black River: An Account of Christmas Preacher, a Slave Freed - Ojabo, Idoko (Auckland University of Technology, 2018)
The PhD comprises a creative component (novel) and critical component (exegesis), and comes out of a desire to fill both a literal and a symbolic gap in the researcher’s family history. The novel, Black River, is in magical realist mode and models elements of Idoma ethnic belief into the slave narrative tradition. It narrates the life of the fictional character, Christmas Preacher, covering five decades of slave experience, from Africa to the United States. His master, Mr. William Preacher, adopts new Quaker doctrines and eventually sets him and two other slaves free. The narrative also incorporates a battle in an external realm between an ageless mermaid-queen and a resurrected ancestor over the life of Christmas. As an emancipated African, he faces the choice of either making Kentucky home or nurturing the sacred revelation that he would one day levitate back to his village in Oli’doma. This extends the slave narrative discourse into the imaginative or speculative realm of a hyperreal lifeworld with the hints of lycanthropy associated with African folklore. The exegesis deploys practice-led journaling as a platform on which three key methodological approaches are employed: the ethnohistorical, the psychogeographical and literary studies. Thus, the groundwork for the novel and the novel itself inform the exegesis, just as the exegesis and the research it embodies informs the novel in a dialogical process of development.
Keywords: Slave narrative; Slave history; African history; African American history; Magical realism; Surrealism; Fantastic; Idoma mythology; Nigerian history; Ethnohistory; Psychogeography; Literary Studies